2021
DOI: 10.5603/ah.a2021.0001
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure lowering effects of alpha-lipoic acid supplementation: a meta-analysis of randomized controlled trials

Abstract: This article is available in open access under Creative Common attribution-non-Commercial-no Derivatives 4.0 international (CC BY-nC-nD 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(66 reference statements)
0
1
0
1
Order By: Relevance
“…The harmful effects of reactive oxygen species have been reported to be neutralized by various functional lipids such as ALA, astaxanthin and squalene (Table 1). Boccardi et al (2021) observed the antioxidant potential of ALA by reduction of the oxidized LDL (Ox-LDL), which is observed to be highly effective against chronic heart injuries. Astaxanthin has strong inhibitory activity against lipid peroxidation mediated by active oxygen species (Xue et al , 2019).…”
Section: Functional Propertiesmentioning
confidence: 99%
“…The harmful effects of reactive oxygen species have been reported to be neutralized by various functional lipids such as ALA, astaxanthin and squalene (Table 1). Boccardi et al (2021) observed the antioxidant potential of ALA by reduction of the oxidized LDL (Ox-LDL), which is observed to be highly effective against chronic heart injuries. Astaxanthin has strong inhibitory activity against lipid peroxidation mediated by active oxygen species (Xue et al , 2019).…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Іншою важливою роллю АЛК є передача сигналів. АЛК активує рецептори інсуліну у відновленому стані, що призводить до каскаду субстратного фосфорилювання та спричиняє транслокацію переносників глюкози із цитоплазми до поверхні клітини [9]. Це робить периферичну глюкозу доступною клітині, а будь-який дефект цього клітинного шляху може призвести до розвитку інсулінорезистентності (ІР) [10].…”
unclassified